2020
DOI: 10.1016/j.ultrasmedbio.2020.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound for Musculoskeletal Applications: A World Federation for Ultrasound in Medicine and Biology Position Paper

Abstract: This World Federation for Ultrasound in Medicine and Biology position paper reviews the diagnostic potential of ultrasound contrast agents for clinical decision-making and provides general advice for optimal contrast-enhanced ultrasound performance in musculoskeletal issues. In this domain, contrast-enhanced ultrasound performance has increasingly been investigated with promising results, but still lacks everyday clinical application and standardized techniques; therefore, experts summarized current knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 102 publications
0
29
0
2
Order By: Relevance
“…The World Federation for Ultrasound in Medicine and Biology (WFUMB), in collaboration with other scientific societies, has produced a series of publications on how to perform contrast-enhanced ultrasound (CEUS; Dietrich et al 2018;Fischer et al 2020). A European Federation of Societies for Ultrasound in Medicine and Biology paper (Jenssen et al 2019) was previously used to outline the rules and actions required to produce technical procedure position papers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Federation for Ultrasound in Medicine and Biology (WFUMB), in collaboration with other scientific societies, has produced a series of publications on how to perform contrast-enhanced ultrasound (CEUS; Dietrich et al 2018;Fischer et al 2020). A European Federation of Societies for Ultrasound in Medicine and Biology paper (Jenssen et al 2019) was previously used to outline the rules and actions required to produce technical procedure position papers.…”
Section: Introductionmentioning
confidence: 99%
“…This position paper slightly differs from another recent WFUMB position paper (Fischer et al 2020), as it combines the efforts of general radiologists, ultrasonologists and neurosurgeons and aims to expand the target audience to both clinical sonologists, who do not have the opportunity to perform intra-operative contrast-enhanced ultrasound (ioCEUS) directly on the exposed brain, and the neurosurgical community, which is less confident with ioCEUS imaging, artifacts, parameters and settings. To this end, general information about ioCEUS imaging is provided along with procedural descriptions, technical tips and intra-operative findings.…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and correct classification are very important to choice the treatment. In routine practice, bone regeneration is evaluated employing several clinical and radiologic criteria such as the absence of pain on weight-bearing and periosteal callus observed on radiograph or computed tomography, which however appears after several weeks [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, studies in human medicine have suggested that the contrast-enhanced ultrasound (CEUS), through gas-filled microbubbles evaluates tissues perfusion and appears useful for the evaluation of bone fracture and surrounding soft tissue microcirculation. Beyond its utility for basic research, CEUS can be also applied in clinical practice for the early detection of neoangiogenesis during the fibrocartilaginous callus formation [1,7,8]. The time-intensity curves parameters, generated during the quantitative analysis of CEUS, has been applied in various musculoskeletal indications, such as in rheumatoid arthritis [9] and for assessment of the post-operative perfusion of muscles and long bones non-union [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines have recently been updated (Dietrich et al 2020a(Dietrich et al , 2020b. More recently musculoskeletal applications for CEUS have been published (Fischer et al 2020). Practical CEUS recommendations for specific organ systems are currently being developed.…”
mentioning
confidence: 99%